Anti-phytopathogenic Bacterial Metabolites From the Seaweed-Derived Fungus Aspergillus sp. D40 - Huang, Rui-Huan; Lin, Wei; Zhang, Peng; Liu, Jian-Yang; Wang, Dan; Li, Yi-Qiang; Wang, Xiao-Qiang; Zhang, Cheng-Sheng; Li, Wei; Zhao, Dong-Lin (Frontiers in Marine Science, 2020)
In order to search for new lead compounds with anti-phytopathogenic bacterial activity, three pairs of new furanone derivatives, sclerotiorumins D–F (1–3), and eight known compounds (4–11) were isolated from the seaweed-derived fungus, Aspergillus sp. D40, fermented with potato dextrose seawater (PDW) medium. Their structures were determined using comprehensive spectroscopic analyses including HRESIMS , 1D and 2D NMR data. Compounds 1–4 and 9 existed as inseparable mixtures of a pair of epimers. Penicillic acid (7) exhibited clear antibacterial activity against Ralstonia solanacearum and several other plant pathogenic bacteria with IC50 values ranging from 11.6 to 58.2 µg/mL.